Workshop Pemanfaatan Quizizz dalam Pembelajaran Matematika di Sekolah - Astuti; Zulfah; Rahma Yenni; Ramdhan; Siti Rohani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Workshop on Using Quizizz in Mathematics Learning in Schools aims to introduce and train educators in using the Quizizz platform as an innovative and interactive learning tool. By using Quizizz, teachers can design interesting, game-based quizzes to increase student motivation and engagement in mathematics learning. This workshop discusses effective ways to integrate Quizizz in various mathematics topics, as well as providing examples of applying quizzes for basic to advanced material. Apart from that, participants are also taught about analyzing quiz results to assess student understanding and design appropriate follow-up. Through this training, it is hoped that teachers can optimize the use of technology in the classroom, enrich students' learning experiences, and create a fun and interactive learning atmosphere.